A time of crises. Consumer co-operatives and their problems around 1990 - Brazda, Johann; Schediwy, Robert
Editors Notes 11 Introduction 13 Johann Brazda and Robert Schediwy Great Britain 45 Franz Müller Germany 139 Johann Brazda Sweden 229 Robert Schediwy Netherlands 341 Johannes Reintjes Switzerland 375 Johanna Setzer Volumne 2 Finland 573 Robert Schediwy France 671 Robert Schediwy Italy 817 Johanna Setzer Austria 900 Robert Blaich Japan 1023 Günter Vacek